Coral Reef Conservation in the Eastern Tropical Pacific - Alvarado Barrientos, Juan José (2017)
This chapter reviews and evaluates coral reef conservation strategies along the eastern tropical Pacific (ETP), a narrow biogeographic region on the Pacific American coast that extends from southern Baja California, Mexico to northern Peru, including several oceanic islands. The ETP is a natural laboratory, a model for understanding the development of coral biotopes in a changing environment. We evaluate conservation strategies in seven countries in the ETP region (Peru was not included for apparent lack of coral habitats). A survey of current Marine Protected Areas (MPAs) highlights great variation in the number, scale and management approaches. Generally, MPAs with no-take areas are relatively uncommon, with multi-purpose areas favored. The Cabo Pulmo MPA in Baja California, Mexico demonstrates that when a local community is involved in the creation and enforcement measures of an MPA, conservation success can be achieved. Despite such apparent successes, inadequate and confusing legal practices have generally forestalled effective protection of coral ecosystems in the ETP. However, in several instances nongovernmental organizations (NGOs) have assisted with planning, negotiation and stakeholder engagement. Nonetheless these findings underscore how the establishment of an MPA does not guarantee that conservation goals will be achieved. This calls for a new approach that incorporates contributions from ecological studies along with a high investment in capacity development and training to ensure that the goals of MPAs better complement effective fisheries and ecosystem management within and outside their borders.